2022
DOI: 10.1021/acs.macromol.2c00339
|View full text |Cite
|
Sign up to set email alerts
|

Complexation between Oppositely Charged Polyelectrolytes in Dilute Solution: Effects of Charge Asymmetry

Abstract: We use dissipative particle dynamics to study polyelectrolyte complexation in dilute solutions under conditions of either chain-length or concentration asymmetry between the polycation and the polyanion, characterized by the macromolecular charge ratio of the minor component to the major component. Our results show that generally the systems form clusters carrying net macromolecular charges. The stoichiometry of these net-charged macromolecular clusters depends on the overall charge asymmetry, and clusters wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 87 publications
1
20
0
Order By: Relevance
“…This electrostatically induced LLPS underpins a number of important biological phenomena such as membraneless organelles in cells ( 3 6 ) and ocean life adhesion ( 7 11 ) and is also being exploited in novel biomedical and biomimetic applications such as drug delivery ( 12 14 ) and underwater adhesion ( 10 , 15 19 ). In the 6 decades since the pioneering theoretical work by Overbeek and Voorn ( 20 ), significant progress has been made on both the theory/simulation and experiment fronts in understanding the many effects on this LLPS, such as chain connectivity ( 21 30 ), excluded volume ( 22 , 25 , 31 35 ), charge sequence ( 36 40 ), ion pairing ( 22 , 41 , 42 ), charge asymmetry ( 43 47 ), temperature ( 48 53 ), pH ( 54 57 ), and solvent quality ( 58 60 ). We refer readers to several excellent recent reviews ( 61 65 ).…”
mentioning
confidence: 99%
“…This electrostatically induced LLPS underpins a number of important biological phenomena such as membraneless organelles in cells ( 3 6 ) and ocean life adhesion ( 7 11 ) and is also being exploited in novel biomedical and biomimetic applications such as drug delivery ( 12 14 ) and underwater adhesion ( 10 , 15 19 ). In the 6 decades since the pioneering theoretical work by Overbeek and Voorn ( 20 ), significant progress has been made on both the theory/simulation and experiment fronts in understanding the many effects on this LLPS, such as chain connectivity ( 21 30 ), excluded volume ( 22 , 25 , 31 35 ), charge sequence ( 36 40 ), ion pairing ( 22 , 41 , 42 ), charge asymmetry ( 43 47 ), temperature ( 48 53 ), pH ( 54 57 ), and solvent quality ( 58 60 ). We refer readers to several excellent recent reviews ( 61 65 ).…”
mentioning
confidence: 99%
“…In reality, the oppositely charged polyions in the supernatant phase are likely to form dispersed clusters made up of two or more polyions. [67][68][69][70][71] Such a distinction undoubtedly influences the behavior of the supernatant near a solid surface. We recognize this as a limitation of our study; however, using a uniformly mixed assumption allows for the complete phase diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By studying both charge- and concentration-asymmetry in PEC systems, Zhen-Gang Wang found that monovalent salts produce a salting-out phenomenon followed by a salting-in phenomenon due to electrostatic screening. 77,88 These results are not in agreement with most of PEMMC systems (salting out was not observed for PEMMCs), indicating that it is not enough to study only one type of asymmetry but to study both types of asymmetries and considering bulky systems. At the moment, the similarities and differences between PEMMCs and asymmetric PECs is far from being understood.…”
Section: Polyelectrolyte-multivalent Molecule Complexesmentioning
confidence: 86%
“…25 On the other hand, if the concentration of charges associated with the multivalent molecule is less than the concentration of charges associated with the polyelectrolyte (non-stoichiometric conditions), the aggregation process results in the formation of clusters that are superficially charged. 88 While the first stage of PEMMC formation is very fast and occurs in the range of seconds, a further slower size-increasing regime takes place, dominated by coalescence or precipitation in a similar way to the formation process of PEC coacervates or precipitates. 29,85 Under specific experimental conditions (highly non-stoichiometric), PEMMCs aggregates display a defined size in the range of a few hundred nanometers and remain relatively stable (do not undergo precipitation) in colloidal suspension (PEMMC nanocomplexes).…”
Section: Polyelectrolyte-multivalent Molecule Complexesmentioning
confidence: 99%
See 1 more Smart Citation